The Effect of Filler on Epoxidised Natural Rubber-Alumina Nanoparticles Composites - Mohamad, Noraiham (eurojournals, 2008)

(untitled)
Epoxidised natural rubber (ENR)-alumina nanoparticles composites (ENRAN) were produced by melt compounding followed by sulphur curing. Alumina nanoparticles were introduced in 10, 20, 30, 40, 50 and 60 parts per hundred rubber (phr) in the compounding recipes to study the effect of filler loading to the cure characteristics and mechanical properties. The dispersion of the alumina nanoparticles was studied using scanning electron microscopy (SEM). The increase in alumina nanoparticles loading in ENR matrices were found to accelerate the curing process up to 40% compared to unfilled ENRs. The minimum torque (ML), maximum torque (MH) and torque difference (MH-ML) also increased due to the increasing crosslink density with the presence of alumina nanoparticles. The increase in alumina nanoparticles content in the ENR compound resulted in the decrease of the tensile strength, elongation at break (EB) and the impact strength but increase the hardness and tensile modulus compared to unfilled ENRs. The alumina particles were observed to be uniformly distributed in the matrices which contributed to the enhancement of MH, ML, tensile modulus and hardness of the ENRANs. When present in the matrix, the particles formed spheres of agglomerates thereby able to effect high filler-matrix interaction which also contribute to the increase in torque values.